CCNA security live lessons a hands-on guide to implementing security on Cisco routers and switches. - Barker, Keith; Safari eBooks ([S.l.] : Pearson Certification, 2012)
Security LiveLessons is a comprehensive video training package covering the key topics on the CCNA Security IINS 640-554 exam. CCIE-certified expert trainer Keith Barker provides you 5 hours of hands-on, step-by-step video training to help you develop the knowledge and skills needed to secure Cisco networks. Through this collection of 10 video training lessons, divided into 33 sublessons, you will gain insight into the hands-on configuration and troubleshooting skills needed to develop a security infrastructure, recognize threats and vulnerabilities to networks, and mitigate security threats. These hands-on video lessons cover hardening network devices with Cisco Configuration Professional (CCP), implementing secure management and monitoring, using ACS and TACACS+, implementing layer 2 protection for switches, packet filtering ACLs, configuring Cisco IOS zone-based firewalls and Cisco ASA firewalls, adding IPS to Cisco routers, connecting IPsec site to site VPN tunnels on Cisco routers, and implementing SSL VPNs on the Cisco ASA. Whether you are looking for helpful and current hands-on labs to supplement your study for the CCNA Security exam or are simply looking to gain a better understanding and proficiency with network security configuration and troubleshooting tasks, CCNA Security 640-554 LiveLessons will help you succeed on the CCNA Security exam and in your daily job as a network security professional."--Resource description page.
Title from title screen.
Presenter, Keith Barker.
Keywords: Computer networks -- Security measures; Routers (Computer networks); Packet switching (Data transmission); Electronic books